Development and Physicochemical Characterization of Hydroxypropylmethylcellulose Patches Containing Derris scandens extract - Watchara Achirasena (Prince of Songkla University, 2025)
Thesis (M.Pharm., Pharmaceutical Sciences)-Prince of Songkla University, 2019